Factors Associated with Knee Arthroplasty in a Knee Osteoarthritis Patient Cohort Treated with Intra-articular Injections of Hylan G-F 20 - Ong, Kevin; Lau, Edmund; Runa, Maria; Daley, William; Altman, Roy (The Journal of Knee Surgery, 2019)
Hylan G-F 20 viscosupplementation can be used to treat knee osteoarthritis pain. This study evaluated time to knee arthroplasty (KA), KA risk factors, and health care resource utilization in patients aged ≥18 years with claims in the Optum Clinformatics Data Mart database (2006–2016) for knee osteoarthritis treated with at least one course of hylan G-F 20. Kaplan–Meier analysis estimated KA risk from osteoarthritis diagnosis and first hylan G-F 20 treatment. KA risk factors were determined using multivariate Cox regression. Among 62,033 patients treated with hylan G-F 20 and/or hylan G-F 20 single intra-articular injection, 60 to 64% did not undergo KA 8 years following first injection. KA risk factors from time of osteoarthritis diagnosis and first hylan G-F 20 treatment were similar: increased age, fewer comorbidities, fewer hylan G-F 20 treatments, female sex, and no ultrasound/fluoroscopy for injection guidance. Patients who underwent KA versus those who did not had more office visits and claims for opioids, nonsteroidal anti-inflammatory drugs, and physical therapy. Patients less likely to undergo KA were younger (<40 years), had more comorbidities, received more courses of hylan G-F 20, were males, or received ultrasound/fluoroscopic injection guidance. Patients who did not receive KA versus those who did used fewer health care resources.
Keywords: knee arthroplasty; osteoarthritis; viscosupplementation; hyaluronic acid; hylan G-F 20